2014
DOI: 10.3174/ajnr.a3830
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Diffusion Tensor Estimation Approach Affects Fiber Tractography of the Fornix in Preterm Brain

Abstract: BACKGROUND AND PURPOSE:Neonatal DTI enables quantitative assessment of microstructural brain properties. Although its use is increasing, it is not widely known that vast differences in tractography results can occur, depending on the diffusion tensor estimation methodology used. Current clinical work appears to be insufficiently focused on data quality and processing of neonatal DTI. To raise awareness about this important processing step, we investigated tractography reconstructions of the fornix with the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…As a result, overlapped regions can be used as a good approximation in group analysis, in particular for TBSS. In turn, a similar effect recently was demonstrated by Plaisier et al Using neonatal DTI dataset they found that FA metric estimated by the nonlinear least squares and RESTORE algorithms has significantly lower values than FA maps evaluated by the ordinary and weighted least squares approaches. As a result, visualized quality of reconstructed tracts based on the RESTORE fitting is significantly higher.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As a result, overlapped regions can be used as a good approximation in group analysis, in particular for TBSS. In turn, a similar effect recently was demonstrated by Plaisier et al Using neonatal DTI dataset they found that FA metric estimated by the nonlinear least squares and RESTORE algorithms has significantly lower values than FA maps evaluated by the ordinary and weighted least squares approaches. As a result, visualized quality of reconstructed tracts based on the RESTORE fitting is significantly higher.…”
Section: Discussionsupporting
confidence: 77%
“…As a result, visualized quality of reconstructed tracts based on the RESTORE fitting is significantly higher. However, all estimations in Ref were performed only by the ExploreDTI package and should be retested in the future by other implementations of used algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Constrained spherical deconvolution (Jeurissen, Leemans, Jones, Tournier, & Sijbers, 2011) was used to compute a whole brain tractogram. Semi-automated tractography (Lebel, Rasmussen, et al, 2008a) was performed to extract the cingulum, fornix, and uncinate fasciculus using regions of interest based on a priori knowledge of tract location (Abdul-Rahman, Qiu, & Sim, 2011;Larroza, Moratal, D'ocon Alcaniz, & Arana, 2014;Lebel, Walker, et al, 2008b;Plaisier et al, 2014;Wakana, Jiang, Nagae-Poetscher, van Zijl, & Mori, 2004). Manual checks of each tract were done to ensure quality of the segmentations and edits were performed when necessary.…”
Section: Brain Imagingmentioning
confidence: 99%
“…An approach combining visual inspection of raw diffusion data with software-based quality checks seems essential to ensure data reliability, as certain types of artifacts can hardly be seen on the diffusion data themselves (Tournier et al, 2011 ; Heemskerk et al, 2013 ). Dependent on the extent of quality loss, datasets need to be excluded from analysis or optimized using artifact and motion correction software in order to prevent inclusion of erroneous diffusion metrics in study results (Chang et al, 2005 ; Veraart et al, 2013 ; Collier et al, 2014 ; Plaisier et al, 2014 ; Tax et al, 2014b ). This especially holds true for advanced neonatal diffusion MRI sequences, as complex acquisition and processing pipelines are accompanied with many pitfalls (Jones and Cercignani, 2010 ; Kersbergen et al, 2014 ).…”
Section: Data Quality and Patient Safetymentioning
confidence: 99%